Skin Autofluorescence Is a Predictor of Cardiovascular Disease in Chronic Kidney Disease Patients. Issue 1 (29th December 2014) - Furuya, Fumihiko; Shimura, Hiroki; Takahashi, Kazuya; Akiyama, Daiichiro; Motosugi, Ai; Ikegishi, Yukinobu; Haraguchi, Kazutaka; Kobayashi, Tetsuro
Abstract Accelerated formation and tissue accumulation of advanced glycation end products (AGEs), reflecting cumulative glycemic and oxidative stress, occurs in age‐related and chronic diseases like diabetes mellitus (DM) and renal failure, and contributes to vascular damage. Skin autofluorescence (AFR), a noninvasive measurement method, reflects tissue accumulation of AGEs. AFR has been reported to be an independent predictor of mortality in Caucasian hemodialysis patients. We assessed the relationship between levels of AFR and the prevalence of cardiovascular disease (CVD), and clarified the prognostic usefulness of skin AFR levels in Asian (non‐Caucasian) hemodialysis (HD) patients. AFR was measured with an autofluorescence reader in 64 HD patients. Overall and cardiovascular mortality was monitored prospectively during the 3‐year follow‐up. During follow‐up, CVD events occurred in 21 patients. The deaths of 10 HD patients were associated with CVD. Multivariate logistic regression analyses showed that initial AFR was an independent risk factor for de novo CVD in HD patients with or without diabetes. When patients were classified on the basis of AFR tertiles, Cochran‐Armitage analysis demonstrated that the highest tertile of AFR level showed an increased odds ratio for the prevalence of CVD. These findings suggest that AFR levels can be used to detect the prevalence of CVD in HD patients with or without diabetes.